Factors Influencing Adherence to Anti-retroviral Therapy in HIV Patients Registered at ART Center Jhansi, Uttar Pradesh - Sharma, Sudha; Bano, Mehar; Malhotra, Anil Kumar (National Journal of Community Medicine, 2022)
Context: After introducing ‘Treat all policy’ in the country and free ART (Anti-retroviral therapy) for all patients the biggest challenge is to optimize adherence to therapy and ensure viral suppression. The present study is aimed to determine the adherence pattern of HIV positive patients at ART center, Jhansi in Uttar Pradesh and to determine the factors influencing adherence. Methods and Material: This cross-sectional study was conducted in an ART Centre of a teaching hospital. In this study 357 patients were interviewed using a modified version of ACTG questionnaire and adherence was calculated by pill count and recall method. Chi square test and logistic regression was done using SPSS. Results: Nearly 72% patients had optimum adherence. On univariate analysis the factors found significant were sex of the patient, the education, the socioeconomic status, financial constraints, family support, WHO stage at diagnosis, alcohol addiction and tobacco addiction. On logistic regression four factors namely having less than college education, WHO stage at diagnosis, alcohol intake and lack of family support were found to predictors of non-adherence. Conclusions: Family support, treatment of alcohol addiction will improve adherence in HIV positive patients.